2009
DOI: 10.1016/j.cub.2008.11.058
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive Paleo-Indian Migration Routes from Beringia Marked by Two Rare mtDNA Haplogroups

Abstract: A dual origin for the first Americans is a striking novelty from the genetic point of view, and it makes plausible a scenario positing that within a rather short period of time, there may have been several entries into the Americas from a dynamically changing Beringian source. Moreover, this implies that most probably more than one language family was carried along with the Paleo-Indians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
401
6
10

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 424 publications
(455 citation statements)
references
References 44 publications
(86 reference statements)
30
401
6
10
Order By: Relevance
“…At that time people in the West were indeed likely to be largely of Beringian origin, consistent with Anzick -also inferred from lower modern-western X rates in mtDNA studies ( Figure 1; see also e.g. Malhi et al 2008, Fig2;Perego et al 2009, fig. 3).…”
Section: Genetics and Culturesupporting
confidence: 82%
See 1 more Smart Citation
“…At that time people in the West were indeed likely to be largely of Beringian origin, consistent with Anzick -also inferred from lower modern-western X rates in mtDNA studies ( Figure 1; see also e.g. Malhi et al 2008, Fig2;Perego et al 2009, fig. 3).…”
Section: Genetics and Culturesupporting
confidence: 82%
“…S1, tree). Three such groups (Wisconsin Chippewa, and N. & S. Ojibwa) have X2a frequencies between 25%-30%, while another 3 Algonquian-speaking groups range from 4-7% (Perego et al 2009 Table S4). Indeed the three primary branch nodes of American X2a (X2a1 ~8.5 ka & X2a2 ~4.4 ka) and X2g: Figure 2) are predominantly represented among Algonquian-speakers, as are the tertiary branches of X2a (7/10: Fernandez et al 2012.…”
Section: Separating Genetics and Culture And Testing Model Predictionsmentioning
confidence: 99%
“…20 In addition, complete mtDNA genome studies have shown that all pan-American mtDNA haplogroups reveal entry times of 15-18 Ka, which are suggestive of a concomitant post-Last Glacial Maximum arrival from Beringia with early Amerindians. [39][40][41][42] As for the question whether the Q1a3*-M346 was present in South Siberia in the post-Last Glacial Maximum, we can report that divergence time estimate for South Siberian versus Chinese/North Pakistan Q1a3*-M346 haplotypes is 15.29 ± 5.49 Ka, thus supporting the idea for the real presence of Q1a3*-M346 in South Siberia in those times.…”
Section: Discussionsupporting
confidence: 65%
“…El avance en las técnicas de análisis molecular que ha tenido lugar en los últimos años ha permitido superar la clásica distinción de cinco haplogrupos (hgs) nativos de América (A, B, C, D y X), identificándose actualmente por lo menos 13 subhaplogrupos que ya estaban diferenciados al momento de ingreso al continente americano (Tamm et al 2007;Malhi et al 2010;Perego et al 2010;Kumar et al 2011), algunos de los cuales presentan patrones de distribución que darían cuenta de distintas rutas de poblamiento, como el caso de D4h3a que se distribuye casi exclusivamente en el oeste del continente, desde Alaska hasta Tierra del Fuego y se asocia con un poblamiento por costa pacífica (Perego et al 2009). Asimismo, al interior de cada subhaplogrupo se está avanzando en la definición de clados con distribuciones geográficas acotadas, que se habrían diferenciado localmente (Gayà-Vidal et al 2011;Bodner et al 2012;de Saint Pierre et al 2012a,b;García et al 2012;Motti, 2012;Taboada-Echalar et al 2013).…”
Section: Antecedentes En Estudios De Adn Mitocondrialunclassified